Towards sustainable agriculture: fossil-free ammonia - Pfromm, Peter H. (My University, 2017)
About 40% of our food would not exist without synthetic ammonia (NH3) for fertilization. Yet, NH3 production is energy intensive. About 2% of the world's commercial energy is consumed as fossil fuels for NH3 synthesis based on the century-old Haber-Bosch (H.-B.) process. The state of the art and the opportunities for reducing the fossil energy footprint of industrial H.-B. NH3 synthesis are discussed. It is shown that even a hypothetical utterly revolutionary H.-B. catalyst could not significantly reduce the energy demand of H.-B. NH3 as this is governed by hydrogen production. Renewable energy-enabled, fossil-free NH3 synthesis is then evaluated based on the exceptional and continuing cost decline of renewable electricity. H.-B. syngas (H2, N2) is assumed to be produced by electrolysis and cryogenic air separation, and then supplied to an existing H.-B. synthesis loop. Fossil-free NH3 could be produced for energy costs of about $232 per tonne NH3 without claiming any economic benefits for the avoidance of about 1.5 tonnes of CO2 released per tonne NH3 compared to the most efficient H.-B. implementations. Research into alternatives to the H.-B. process might be best targeted at emerging markets with currently little NH3 synthesis capacity but significant future population growth such as Africa. Reduced capital intensity, good scale-down economics, tolerance for process upsets and contamination, and intermittent operability are some desirable characteristics of NH3 synthesis in less developed markets, and for stranded resources. Processes that are fundamentally different from H.-B. may come to the fore under these specific boundary conditions.
Citation: Pfromm, P. H. (2017). Towards sustainable agriculture: Fossil-free ammonia. Journal of Renewable and Sustainable Energy, 9(3), 034702. https://doi.org/10.1063/1.4985090
Keywords: Ammonia; Haber-Bosch; Renewable; Fossil-free; Fertilizer; Economical